2018
DOI: 10.1177/155892501801300305
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Characteristics of Aluminum Sputtered Fabrics

Abstract: Al was sputtered onto four substrates: nylon, polyester, cotton/polyester, and shape memory polyurethane nanoweb, and the heat-transfer characteristics of the resultant materials were investigated by surface temperature measurements. The thickness of the Al layer increased linearly with sputtering time. The heat-transfer mechanisms of the multilayer systems in terms of conduction, convection, and radiation were investigated under steady-state conditions using a hot plate as a heat source in contact with Al-spu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The heat transfer rate calculated by this study model was derived through Equations (1)-(3) above, resulting in Equation (4). 28 As seen in Figure 1 and Equation 4, the heat transfer theory by conduction was used for calculation in the case of Material 1. Heat transfer theories by convection and radiation were used for the calculation of Material 2…”
Section: Theoretical Background: Conduction Convection and Radiationmentioning
confidence: 99%
See 2 more Smart Citations
“…The heat transfer rate calculated by this study model was derived through Equations (1)-(3) above, resulting in Equation (4). 28 As seen in Figure 1 and Equation 4, the heat transfer theory by conduction was used for calculation in the case of Material 1. Heat transfer theories by convection and radiation were used for the calculation of Material 2…”
Section: Theoretical Background: Conduction Convection and Radiationmentioning
confidence: 99%
“…The numerical values used for calculation are shown in Table 3. In the case of thickness, the actual measured values were used, and in the case of metal thermal conductivity and emissivity, reference values 28,32 were employed. Also, such reference values were utilized for the nylon fabric's thermal conductivity, emissivity, and heat transfer coefficient.…”
Section: Theoretical Analysis Of Heat Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…The value of SiO 2 /Al/SiO 2 reflection coefficient was 64.97%, for SiO 2 /Al was 57.38%, and for a single Al was 51.59%, respectively. Another example is the study of heat transfer in textile materials sputtered with the aluminum [9]. Four textile substrates were selected for testing: polyester, nylon, cotton blend with 50/50 polyester, and polyurethane with the shape memory.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the sputtering treatment could give significant effects to the heat transfer of nylon without much loss in its shear and bending property, as well as water vapor transmission. The sputtered aluminum fabric was also studied for changes in its heat transfer [16]. Aluminum was applied onto four textile substrates: nylon, polyester, cotton blend with 50/50 polyester, and shape memory polyurethane.…”
mentioning
confidence: 99%